Self-Competence Development Strategy for UNPAB Postgraduate Students - Mesra B; Risliana Octavia Siregar (International Journal of Management, Economic and Accounting, 2025)
Self-competence development is an important aspect in improving the quality of human resources at the postgraduate education level. This study aims to analyze the self-competency development strategies of Postgraduate students of the Master of Management Study Program, Universitas Pembangunan Panca Budi (UNPAB) as well as their supporting and inhibiting factors This study uses a qualitative approach with a case study design. Data were obtained through in-depth interviews, limited observations, and documentation of postgraduate students of the UNPAB master's program of management who were selected purposively. Data analysis was carried out using the Miles and Huberman interactive model.The results of the study show that the development of self-competence is carried out through strengthening hard skills and soft skills at the same time. Hard skills are developed through academic activities and research, while soft skills are developed through discussions, presentations, teamwork, and time management. Intrinsic motivation and support of the academic environment are the main supporting factors, while time constraints and workload are the inhibiting factors. This study confirms that the development of self-competence of postgraduate students is influenced by the readiness of individuals as adult learners and institutional support.